2021
DOI: 10.20411/pai.v6i2.482
|View full text |Cite
|
Sign up to set email alerts
|

A Patient With Multiple Carbapenemase Producers Including an Unusual Citrobacter sedlakii Hosting an IncC blaNDM-1- and armA-carrying Plasmid

Abstract: Background. Patients colonized with multiple species of carbapenemase-producing Enterobacterales (CPE) are increasingly observed. This phenomenon can be due to the high local prevalence of these pathogens, the presence of important host risk factors, and the great genetic promiscuity of some carbapenemase genes. Methods. We analyzed 4 CPE (Escherichia coli, Klebsiella pneumoniae, Providencia stuartii, Citrobacter sedlakii), 1 extended-spectrum cephalosporin-resistant K. pneumoniae (ESC-R-Kp), and 1 carbapenema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The nearest ancestor plasmid, calculated by BLASTn (Percent Query Coverage: 86%; Percent Identity: 99.95%, for BRIG visualisation see Figure 1 ), was isolated in 2020 in Switzerland (NCBI GenBank accession no. CP071077.1, plasmid p3347558_4) [ 18 ]. Overall, these results strongly suggest horizontal plasmid transfer has occurred between these two strains at one point in the past.…”
Section: Resultsmentioning
confidence: 99%
“…The nearest ancestor plasmid, calculated by BLASTn (Percent Query Coverage: 86%; Percent Identity: 99.95%, for BRIG visualisation see Figure 1 ), was isolated in 2020 in Switzerland (NCBI GenBank accession no. CP071077.1, plasmid p3347558_4) [ 18 ]. Overall, these results strongly suggest horizontal plasmid transfer has occurred between these two strains at one point in the past.…”
Section: Resultsmentioning
confidence: 99%
“…In another study (2008)(2009), transmission from infants colonized with CTX-M-15-Kp during an NICU outbreak to parents/relatives was also observed in 32% of the households [156]. It should also be noted that there are numerous accounts in the literature of colonized patients hospitalized in other institutions (including abroad) who imported MDR-Ent to low-prevalence countries [177][178][179][180][181]. These patients can transmit their MDR-Ent and consequently generate outbreaks.…”
Section: Contribution To the Transmission Of Mdr-entmentioning
confidence: 98%
“…A number of studies reported that few ANT(3") enzymes, encoded by aadA (aadA1, aadA2, aadA16), conferred resistance to spectinomycin and streptomycin in Citrobacter spp. (Babiker et al, 2020;Ramsamy et al, 2020;Moser et al, 2021;Han et al, 2022;Luo et al, 2022). The presence of streptomycin inactivating genes (strA, strB) was also reported in Citrobacter spp.…”
Section: Antibiotic Resistancementioning
confidence: 93%
“…The isolate showed reduced susceptibility to carbapenems, 3 r d and 4 t h -generation cephalosporins, aminoglycoside, trimethoprim-sulfamethoxazole, and colistin (Faccone et al, 2019). Moreover, the bla NDM-1 , found to coexist with armA in the C. sedlakii strain, isolated from the same patient, is another example of conferring resistance to a broad range of antibiotics, including carbapenems and aminoglycosides via horizontal transfer (Moser et al, 2021). Co-existence of bla NDM-1 with bla SHV-12 on the same transferrable IncX3 plasmid pZY-NDM1 in C. freundii and co-production of NDM-1 and OXA-10 in C. braakii isolate on different plasmids was also reported (Zhang et al, 2021;Han et al, 2022).…”
Section: Antibiotic Resistancementioning
confidence: 95%
See 1 more Smart Citation